2016
DOI: 10.3201/eid2202.150051
|View full text |Cite
|
Sign up to set email alerts
|

Trematode FlukeProcerovumvariumas Cause of Ocular Inflammation in Children, South India

Abstract: Larvae of this fluke are novel causes of granulomatous eye disease in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…The ITS2 gene gives positive bands at 539bp that confirm that the parasite sample is trematode. These results were similar to that obtained by Arya et al (2016). In…”
Section: Discussionsupporting
confidence: 92%
“…The ITS2 gene gives positive bands at 539bp that confirm that the parasite sample is trematode. These results were similar to that obtained by Arya et al (2016). In…”
Section: Discussionsupporting
confidence: 92%
“…Uveitis from the trematode fluke Procerum varium from snails has been reported from a case series in South India. There is also a report of Mycobacterium chelonae infections from contaminated humidifiers 88, 89, 90, 91, 92…”
Section: Specific Water-borne Ocular Infectionsmentioning
confidence: 99%
“…Only a few pediatric cases are reported from India. [158][159][160] Diagnosis is confirmed by detection of antibodies in serum or aqueous and vitreous sample by ELISA. 158…”
Section: Toxocariasismentioning
confidence: 99%
“…In a recent study, a trematode Procerovum varium was identified as a cause of ocular granuloma that developed in children who bathed in ponds or rivers in South India. 159 Birds act as definitive hosts and parasite eggs are discharged in their feces. The eggs hatch to release freely swimming miracidia, which infect first intermediate hosts, that is, snails.…”
Section: Procerovum Variummentioning
confidence: 99%